Uncertainty, Self-efficacy, and Self-care Behavior in Patients With Breast Cancer Undergoing Chemotherapy in China. Issue 3 (May 2015) - Zhang, Yingzi; Kwekkeboom, Kristine; Petrini, Marcia
Abstract : Background: Treatment for breast cancer causes uncertainty in the face of new and distressing experiences and often results in the need for self-care. Identifying how uncertainty influences self-care behavior is essential to design interventions that enhance self-care capacity and improve patient outcomes. Objectives: The aims of this study were to describe the levels of uncertainty, self-efficacy, and self-care behavior in Chinese women receiving chemotherapy for breast cancer and to determine if self-efficacy mediates the relationship between uncertainty and self-care behavior. Methods: A cross-sectional descriptive correlational design was used. Ninety-seven participants completed the Generalized Self-efficacy Scale, the Mishel Uncertainty in Illness Scale, and the Appraisal of Self-care Agency Scale–Revised. Descriptive statistics were used to analyze the levels of uncertainty, self-efficacy, and self-care behaviors in the sample. Multiple regression was used to test the mediating effect of self-efficacy in the relationship between uncertainty and self-care behavior. Results: Mean ratings of uncertainty (76.70), self-efficacy (27.15), and self-care behavior (53.96) all fell in the moderate range. Both uncertainty and self-efficacy independently predicted self-care behavior, explaining 18.2% of the variance, but self-efficacy did not mediate the relationship between uncertainty and self-care behavior. Conclusions: Research is needed to further evaluate the proposed relationships using instruments specific to/related to cancer and evaluate change over time. Self-care interventions that have been efficacious in Western populations could be revised to assist Chinese women to reduce uncertainty and enhance self-efficacy in coping with breast cancer. Implications for Practice: Self-care intervention programs should include strategies to reduce uncertainty and enhance self-efficacy in coping with breast cancer treatment.